Identifying and Explaining the Prerequisites and Consequences of Political Acuity of State Managers Using the Fuzzy Delphi Approach - seyyed jafar zonoozi; Meysam Jafari (مطالعات منابع انسانی, 2021)
Background & Purpose: The lack of precise criteria for promotion as well as ambiguous organizational goals have caused both the process of career path development and the outlined prospects achievement difficult. Nevertheless, managers, who have political acuity, achieve their goals by properly analyzing the organization, establishing strategic relationships, and managing key persons in the organization. The purpose of this study is to identify and explain the prerequisites and consequences of political acuity of state managers.Methodology: This study is applied in terms of purpose and descriptive survey regarding data collection. Furthermore, this study used qualitative-quantitative mixed approach in the deductive-inductive paradigm. The participants who were involved in the qualitative phase were 18 professors of management and political science selected via purposive sampling and the extracted data was analyzed using theme analysis. Besides, 29 middle managers from governmental organizations in West Azerbaijan Province were chosen to take part in the quantitative phase using a non-probability sampling method.Findings: In the qualitative phase, the data obtained from the interviews were analyzed via theme analysis using ATLAS.ti software, and the quantitative phase of the research in addition to the final analysis were conducted using the Fuzzy Delphi Method. Using qualitative data obtained from exploratory interviews, the prerequisites and consequences of political managers were identified in the form of 24 factors, then by extracting these factors, they were ranked through quantitative research.Conclusion: The results revealed that influence tactics learning, knowledge of way the system works, political knowledge and skill, foresight and analysis of the environment and atmosphere of the organization are the most important prerequisites of political acuity of government managers. Also, among the most important consequences of political acuity of government managers are job security, hierarchical promotion, formation of beneficial coalitions, and organizational acceptance.